A high-hygroscopic, porous pH-colorimetric label based on κ-carrageenan and carboxymethyl cellulose composite cryogel for monitoring pork freshness - Yalu Yun; Xiling Cheng; Jin Xu; Yuxi Wang; Hailan Jin; Jian Li; Lijuan Wang (Food Hydrocolloids, 2025)

Eco-friendly fabricating Tara pod extract-soy protein isolate film with antioxidant and heat-sealing properties for packaging beef tallow - Zihao Ren; Yuping Ning; Jin Xu; Xiling Cheng; Lijuan Wang (Food Hydrocolloids, 2024)

Short-term residential exposure to air pollution and risk of acute myocardial infarction deaths at home in China - Jian Cheng; Hao Zheng; Jing Wei; Cunrui Huang; Hung Chak Ho; Shengzhi Sun; Dung Phung; Ho Kim; Xiling Wang; Zhongliang Bai; Mohammad Zahid Hossain; Shilu Tong; et al. (Environmental Science and Pollution Research, 2023)
Air pollution remains a major threat to cardiovascular health and most acute myocardial infarction (AMI) deaths occur at home. However, currently established knowledge on the deleterious effect of air pollution on AMI has been limited to routinely monitored air pollutants and overlooked the place of death. In this study, we examined the association between short-term residential exposure to China’s routinely monitored and unmonitored air pollutants and the risk of AMI deaths at home. A time-stratified case-crossover analysis was undertaken to associate short-term residential exposure to air pollution with 0.1 million AMI deaths at home in Jiangsu Province (China) during 2016–2019. Individual-level residential exposure to five unmonitored and monitored air pollutants including PM 1 (particulate matter with an aerodynamic diameter ≤ 1 μm) and PM 2.5 (particulate matter with an aerodynamic diameter ≤ 2.5 μm), SO 2 (sulfur dioxide), NO 2 (nitrogen dioxide), and O 3 (ozone) was estimated from satellite remote sensing and machine learning technique. We found that exposure to five air pollutants, even below the recently released stricter air quality standards of the World Health Organization (WHO), was all associated with increased odds of AMI deaths at home. The odds of AMI deaths increased by 20% (95% confidence interval: 8 to 33%), 22% (12 to 33%), 14% (2 to 27%), 13% (3 to 25%), and 7% (3 to 12%) for an interquartile range increase in PM 1 , PM 2.5 , SO 2 , NO 2 , and O 3 , respectively. A greater magnitude of association between NO 2 or O 3 and AMI deaths was observed in females and in the warm season. The greatest association between PM 1 and AMI deaths was found in individuals aged ≤ 64 years. This study for the first time suggests that residential exposure to routinely monitored and unmonitored air pollutants, even below the newest WHO air quality standards, is still associated with higher odds of AMI deaths at home. Future studies are warranted to understand the biological mechanisms behind the triggering of AMI deaths by air pollution exposure, to develop intervention strategies to reduce AMI deaths triggered by air pollution exposure, and to evaluate the cost-effectiveness, accessibility, and sustainability of these intervention strategies. Graphical abstract

Urban-rural disparity in heatwave effects on diabetes mortality in eastern China: A case-crossover analysis in 2016–2019 - Junwen Tao; Hao Zheng; Hung Chak Ho; Xiling Wang; Mohammad Zahid Hossain; Zhongliang Bai; Ning Wang; Hong Su; Zhiwei Xu; Jian Cheng (Science of The Total Environment, 2023)

Exogenous melatonin alleviates damage from drought stress in Brassica napus L. (rapeseed) seedlings - Jingjing Li; Liu Zeng; Yong Cheng; Guangyuan Lu; Guiping Fu; Haiqing Ma; Qingyun Liu; Xuekun Zhang; Xiling Zou; Chunsheng Li (Acta Physiologiae Plantarum, 2018)

Ethanol content in plants of Brassica napus L. correlated with waterlogging tolerance index and regulated by lactate dehydrogenase and citrate synthase - Benbo Xu; Yong Cheng; Xiling Zou; Xuekun Zhang (Acta Physiologiae Plantarum, 2016)

Establishment and characterization of multi-drug resistant, prostate carcinoma-initiating stem-like cells from human prostate cancer cell lines 22RV1 - Te Liu; Fuhui Xu; Xiling Du; Dongmei Lai; Tianjin Liu; Yarui Zhao; Qin Huang; Lizhen Jiang; Wenbin Huang; Weiwei Cheng; Zhixue Liu (Molecular and Cellular Biochemistry, 2010)